EIS Evaluation of corrosion resistance of AISI 304 stainless steel exposed to Pseudomonas Stutzeri, - Galicia, Monica (2021)
In this work, the formation of a Pseudomonas stutzeri biofilm in a marine medium on AISI 304 stainless steel was observed to evaluate the effects of biofilm formation on metallic passivation and corrosion processes. Open circuit potential and electrochemical impedance measurements were carried out for 21 days on abiotic and biotic electrochemical cells. The influence of biofilm formation on corrosion potential was monitored and used to propose a mechanism based on the impedance and corrosion resistance values. In the abiotic cell, the corrosion resistance varied periodically, which was attributed to the electrolytic activity of the medium on the metal. However, corrosion resistance increased in the presence of bacteria and continued to increase as immersion time increased. Exopolymeric substances were deposited onto the electrode, suggesting that P. stutzeri RPh9 colonized the metallic surface, passivating the stainless steel electrode surface through continuous biofilm formation. Detachment of the biofilm on day 21 was the likely cause of decreased corrosion resistance at the end of the experiment.